The Effect of Rational Emotive Behavior Therapy (REBT) on Antiretroviral Therapeutic Adherence and Mental Health in Women Infected with HIV/AIDS - Surilena Surilena; R Irawati Ismail; Irwanto Irwanto; Zubairi Djoerban; Budi Utomo; Sabarinah Sabarinah; Iwan Iwan; Arwin A.P. Akip (Acta Medica Indonesiana)
Aim: to identify the effectiveness of rational-emotive-behavior-based therapy (REBT-based therapy) on improved mental health and antiretroviral (ART) therapeutic adherence in women infected with HIV/AIDS (female subjects with HIV/AIDS). Methods: a randomized and single-blinded clinical trial in women infected with HIV/AIDS who had their treatment at the outpatient clinic of Pokdiksus AIDS RSCM and at the AIDS Comprehensive Diagnostic Unit of Dharmais Hospital was conducted between October 2011 and March 2012. A block randomization of 160 female subjects with AIDS was performed that resulted in a REBT-based treatment group (n=80) and a control group (n=80). The treatment group received REBT-based intervention of 8 sessions weekly including 6 individual-therapeutic sessions/week and 2 group-therapeutic sessions /week. Instruments used in the study were questionnaires on demography, ART adherence (measured by self report and pill count), and mental health (SRQ-20). Data were analyzed using Chi-Square test, Generalized Linear Model, and Generalized Estimating Equations. Results: there were 148 respondents analyzed including in the REBT-based group (n=72) and in the control group (n=76) with mean age of 33-34 years. After 8 weeks of REBT-based intervention, there was improved (increased) mean value of the self-reported adherence score (self-report) compared to control group (100%; CI 95%,83.3-96.7 vs. 84%; CI 95%,77.5-87.8) and improved (decreased) SRQ-20 mean score in REBT-based treatment group compared to control group (2.9; CI 95%, 2.7-13.0 vs. 5.4; CI 95%: 5.0.-13.6). ART adherence based on viral load titer was not analyzed in both group since most of VL titer were undetected (<400 copies/mL). GLM analysis showed decreased SRQ-20 mean score and increased mean value of self-reported ART adherence (self-report) in the REBT-based treatment group, which were more significant (p<0.000) than control group on the 8th week. GEE analysis showed that 1 point decrement of SRQ-20 would increase self-reported ART adherence as much as 0.722 point and the correlation was statistically significant (p<0.00). Conclusion: after 8 weeks of REBT- based intervention to female subjects with HIV/AIDS, there is a decrease of SRQ-20 mean score which may result in increased ART adherence mean score in the treatment group compared to the control.